2014
DOI: 10.1128/cvi.00444-14
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Protein Comprising Factor H Domains 6 and 7 and Human IgG1 Fc as an Antibacterial Immunotherapeutic

Abstract: bThe emergence of antimicrobial resistance among several medically important pathogens represents a serious threat to human health globally and necessitates the development of novel therapeutics. Complement forms a key arm of innate immune defenses against invading pathogens. A mechanism of complement evasion employed by many pathogens is binding of complement inhibitors, including factor H (FH), a key downregulator of the alternative pathway. Most FH-binding bacteria engage FH through regions in FH spanned by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…FH domain 6,7 binds to FHbp (35), to NspA (17), and to some PorB2 amino acid sequence variants (32). In previous studies, we found that recombinant fragments of FH domains 6 and 7 fused to mouse IgG2a or human IgG1 (FH6,7/Fc) bound with higher affinity than fulllength human FH (32,36). Therefore, we used a human FH6,7/ mouse Fc fragment and flow cytometry to probe binding of the double FHbp/NspA KO mutants.…”
Section: Resultsmentioning
confidence: 99%
“…FH domain 6,7 binds to FHbp (35), to NspA (17), and to some PorB2 amino acid sequence variants (32). In previous studies, we found that recombinant fragments of FH domains 6 and 7 fused to mouse IgG2a or human IgG1 (FH6,7/Fc) bound with higher affinity than fulllength human FH (32,36). Therefore, we used a human FH6,7/ mouse Fc fragment and flow cytometry to probe binding of the double FHbp/NspA KO mutants.…”
Section: Resultsmentioning
confidence: 99%
“…The recombinant fragments were similar to those described previously (21) except that mouse IgG2a Fc had been replaced by human IgG1 Fc (22). For inhibition of FH binding, the recombinant fragments (50 g/ml) in Dulbecco's PBS (DPBS) containing 1% bovine serum albumin (BSA) together with macaque serum (1:10 dilution) were incubated with bacteria for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Binding of FH/Fc to bacteria and C3 fragments deposited on bacteria were measured by flow cytometry as described previously (35). Data were acquired on a LSRII flow cytometer and data were analyzed using FlowJo software.…”
Section: Methodsmentioning
confidence: 99%